mRNA Expression of Interferon Regulatory Factors during Acute Rejection of Liver Transplants in Patients with Autoimmune Hepatitis - Nasiri, M. (Int J Organ Transplant Med, 2018)
BACKGROUND: Interferon regulatory factors (IRFs) can play a critical role in the regulation of many facets of innate and adaptive immune responses through transcriptional activation of type I interferons, other proinflammatory cytokines, and chemokines. However, their roles in transplantation immunity still remain to be elucidated. OBJECTIVE: To evaluate the time course of mRNA expression of all 9 members of IRFs family of transcription factors during liver allograft acute rejection. METHODS: Blood samples of 19 patients with autoimmune hepatitis receiving liver transplants were collected on days 1, 3, 5, and 7 post-transplantation. The patients were followed for 6 months after transplantation and divided into two groups of acute rejection (AR) (n=4) and non-acute rejection (non-AR) (n=15). RESULTS: All of the studied transcription factors were down-regulated in AR-group on days 3, 5, and 7 post-transplantation compared to non-AR group. The mean±SEM IRF5 on day 7 post-transplantation was significantly (p=0.005) lower in AR-group than in non-AR group (0.7±0.21 vs. 1.91±0.27, respectively); expression of other IRFs family members was not significantly different between the two groups on days 3, 5, and 7 post-transplantation. CONCLUSION: IRF5 may have an important role during the acute rejection of liver transplants.